Conservation of Plasmid DNA Sequences in Coronatine-Producing Pathovars of Pseudomonas syringae - Bender, Carol L. (1991)
In Pseudomonas syringae pv. tomato PT23.2, plasmid pPT23A (101 kb) is involved in synthesis of the phytotoxin coronatine (C. L. Bender, D. K. Malvick, and R. E. Mitchell, J. Bacteriol. 171:807-812, 1989). The physical characterization of mutations that abolished coronatine production indicated that at least 30 kb of pPT23A DNA are required for toxin synthesis. In the present study, (32)P-labeled DNA fragments from the 30-kb region of pPT23A hybridized to plasmid DNAs from several coronatine-producing pathovars of P. syringae under conditions of high stringency. These experiments indicated that this region of pPT23A was strongly conserved in large plasmids (90 to 105 kb) that reside in P. syringae pv. atropurpurea, glycinea, and morsprunorum. The functional significance of the observed homology was demonstrated in marker-exchange experiments in which Tn5-inactivated sequences from the 30-kb region of pPT23A were used to mutate coronatine synthesis genes in the three heterologous pathovars. Physical characterization of the Tn5 insertions generated by marker exchange indicated that genes controlling coronatine synthesis in P. syringae pv. atropurpurea 1304, glycinea 4180, and morsprunorum 567 and 3714 were located on the large indigenous plasmids where homology was originally detected. Therefore, coronatine biosynthesis genes are strongly conserved in the plasmid DNAs of four producing pathovars, despite their disparate origins (California, Japan, New Zealand, Great Britain, and Italy).